Diaphragmatic breathing during virtual reality exposure therapy for aviophobia: functional coping strategy or avoidance behavior? a pilot study. Issue 1 (December 2017) - Shiban, Youssef; Diemer, Julia; Müller, Jana; Brütting-Schick, Johanna; Pauli, Paul; Mühlberger, Andreas
Abstract Background Although there is solid evidence for the efficacy of in vivo and virtual reality (VR) exposure therapy for a specific phobia, there is a significant debate over whether techniques promoting distraction or relaxation have impairing or enhancing effects on treatment outcome. In the present pilot study, we investigated the effect of diaphragmatic breathing (DB) as a relaxation technique during VR exposure treatment. Method Twenty-nine patients with aviophobia were randomly assigned to VR exposure treatment either with or without diaphragmatic breathing (six cycles per minute). Subjective fear ratings, heart rate and skin conductance were assessed as indicators of fear during both the exposure and the test session one week later. Results The group that experienced VR exposure combined with diaphragmatic breathing showed a higher tendency to effectively overcome the fear of flying. Psychophysiological measures of fear decreased and self-efficacy increased in both groups with no significant difference between the groups. Conclusions Our findings indicate that diaphragmatic breathing during VR exposure does not interfere with the treatment outcome and may even enhance treatment effects of VR exposure therapy for aviophobic patients. Trial registration Retrospectively registered. ClinicalTrials.govNCT02990208 . Registered 07 December 2016.